Household Enterprises in Vietnam : Survival, Growth, and Living Sandards - Vijverberg, Wim P. M.; Haughton, Jonathan (World Bank, Washington, DC, 2013)
In Vietnam almost a quarter of adults worked in nonfarm household enterprises in 1998. Based on household panel data from the Vietnam Living Standards Surveys of 1993 and 1998, the authors find some evidence that operating an enterprise leads to greater affluence. The data show that nonfarm household enterprises are most likely to be operated by urban households, by those with moderately good education, and by the children of proprietors. The authors were able to construct a panel of nonfarm household enterprises; 39 percent of enterprises operating in 1993 were still in business in 1998. Those in the (more affluent) south of the country were less likely to survive, as were smaller and younger businesses. A pattern emerges from the data. In poor areas the lack of education, credit, and effective demand limits the development of nonfarm household enterprises. In rich areas there is the attraction of wage labor. Nonfarm household enterprises are thus most important in the period of transition, when agriculture is declining in importance but before the formal sector becomes established. The authors expect these enterprises to continue to play a modest supporting role in fostering economic growth in Vietnam.